Impact of clear aligners on gingivitis incidence and prevention strategies in adolescents and adults: a prospective observational study - Haiying Zhang; Shuangyan Bi; Xiaojun Zhang (BMC Oral Health)
Abstract Objective This study aims to analyze the differences in gingivitis incidence among adolescents and adults using clear aligners for orthodontic correction and to evaluate the effectiveness of prevention strategies on orthodontic outcomes. Methods This observational study included 120 patients undergoing clear aligner orthodontic treatment from June 2018 to September 2023. Participants were divided into an adolescent group (66 cases) and an adult group (54 cases), each further split into a study group and a control group. The control group patients maintained their daily lifestyle throughout the study period. The study group received personalized oral hygiene education and guidance on self-oral care techniques at each follow-up visit. Routine periodontal treatment and personalized oral hygiene education were provided, and the incidence of gingivitis was evaluated six months post-treatment. Statistical methods, including chi-square tests for categorical data, t-tests for continuous variables, and two-way ANOVA for group comparisons, were employed to ensure the robustness of the results. Results The incidence of gingivitis was significantly higher in the adolescent group compared to the adult group (P < 0.05). Specifically, within the adolescent group, the study group exhibited a higher gingival index (GI) than the control group (P < 0.05), while the difference in the adult group was not significant. Conclusion During clear aligner orthodontic treatment, adolescents are more prone to developing gingivitis than adults. Additionally, basic periodontal therapy, as opposed to verbal oral health education alone, can moderately reduce the incidence of gingivitis in clear aligner patients during treatment.